Expression Profiles of Circulating microRNAs in South African Type 2 Diabetic Individuals on Treatment - Weale, Cecil J.; Matshazi, Don M.; Davids, Saarah F. G.; Raghubeer, Shanel; Erasmus, Rajiv T.; Kengne, Andre P.; Davison, Glenda M.; Matsha, Tandi E. (Frontiers in Genetics, 2021)
Aim: The influence of disease duration and anti-diabetic treatment on epigenetic processes has been described, with limited focus on interactions with microRNAs (miRNAs). miRNAs have been found to play key roles in the regulation of pathways associated with type 2 diabetes mellitus (T2DM), and expression patterns in response to treatment may further promote their use as therapeutic targets in T2DM and its associated complications. We therefore aimed to investigate the expressions of circulating miRNAs (miR-30a-5p, -1299, -182-5p, -30e-3p and -126-3p) in newly diagnosed and known diabetics on treatment, in South Africa. Methods: 1254 participants with an average age of 53.8 years were included in the study and classified according to glycaemic status (974 normotolerant, 92 screen-detected diabetes and 188 known diabetes). Whole blood levels of miR-30a-5p, miR-1299, miR-182-5p, miR-30e-3p and miR-126-3p were quantitated using RT-qPCR. Expression analysis was performed and compared across groups. Results: All miRNAs were significantly overexpressed in subjects with known diabetes when compared to normotolerant individuals, as well as known diabetics versus screen-detected (p<0.001). Upon performing regression analysis, of all miRNAs, only miR-182-5p remained associated with the duration of the disease after adjustment for type of treatment, (OR: 0.127, CI: 0.018-0.236, p=0.023). Conclusions: Our findings revealed important associations and altered expression-patterns of miR-30a-5p, -1299, -182-5p, -30e-3p and -126-3p in known diabetics on anti-diabetic treatment compared to newly diagnosed individuals. Additionally, miR-182-5p expression decreased with increasing duration of T2DM. Further studies are however recommended to shed light on the involvement of the miRNA in insulin signalling and glucose homeostasis, to endorse its use as a therapeutic target in DM and its associated complications.